2016
DOI: 10.1039/c6me00061d
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the molecular basis for the controlled design of ruthenium nanoparticles in microporous aluminophosphates

Abstract: Controling the structural properties of nanoparticle catalysts within a microporous framework is a major challenge. Using in situ X-ray Absorption Fine Structure (XAFS) Spectroscopy we detail the influence of activation parameters on the nature of ruthenium particles that are located within the confines of a nanoporous aluminophosphate (RuAlPO-5) architecture. These in situ studies confirm that controlled annealing conditions can tailor the formation of specific ruthenium species, which alter the catalytic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Co, Ru or Zn) can be readily distinguished from the lighter atoms in the gel. 20,23,24 This has allowed groups to observe the progression from the metal salt precursor, to tetrahedral framework species, coinciding with the framework formation. Al XAS studies have also been reported; however these were limited to XANES analysis, due to the lower energy required.…”
Section: Introductionmentioning
confidence: 98%
“…Co, Ru or Zn) can be readily distinguished from the lighter atoms in the gel. 20,23,24 This has allowed groups to observe the progression from the metal salt precursor, to tetrahedral framework species, coinciding with the framework formation. Al XAS studies have also been reported; however these were limited to XANES analysis, due to the lower energy required.…”
Section: Introductionmentioning
confidence: 98%
“…However, due to the limited pore aperture and channels of these systems, even sub-nanometre particles can block the framework and hinder activity, thereby preventing reagents from accessing the internal active sites. In contrast, mesoporous species (pores greater than 2 nm) maintain a large portion of their porosity when hosting metal nanoparticles, although they lack the more subtle ability to control the space around the active site [13]. In our previous work we have shown that inclusion of a micellular agent, i.e., dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (DMOD) in an AlPO synthesis, alongside a microporous template, allows silanol-lined mesopores to form simultaneously with the microporous network, yielding a hierarchically porous (HP) system [14].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, mesoporous species (pores > 2 nm) maintain a large portion of their porosity when hosting metal nanoparticles, though lack the more subtle ability to control the space around the active site. [13] In our previous work we have shown that inclusion of a micellular agent; DMOD (Dimethyloctadecyl [3-(trimethoxysilyl)propyl] Ammonium Chloride) in an AlPO synthesis, alongside a microporous template, allows silanol-lined mesopores, to form simultaneously, alongside with the microporous network, yielding a hierarchically porous (HP) system. [14] In this work we utilise both a HP silicon-doped aluminophosphate (SAPO) system and a traditional microporous SAPO-5 species, to demonstrate the advantages of hierarchical systems for nanoparticle deposition.…”
Section: Resultsmentioning
confidence: 99%